2019
DOI: 10.2196/13229
|View full text |Cite
|
Sign up to set email alerts
|

A Hospital-Community-Family–Based Telehealth Program for Patients With Chronic Heart Failure: Single-Arm, Prospective Feasibility Study

Abstract: BackgroundAn increasing number of patients with chronic heart failure (CHF) are demanding more convenient and efficient modern health care systems, especially in remote areas away from central cities. Telehealth is receiving increasing attention, which may be useful to patients with CHF.ObjectiveThis study aimed to evaluate the feasibility of a hospital-community-family (HCF)–based telehealth program, which was designed to implement remote hierarchical management in patients with CHF.MethodsThis was a single-a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
111
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(124 citation statements)
references
References 34 publications
(32 reference statements)
1
111
0
12
Order By: Relevance
“…There are scarce data on the implementation of such an integrated program to manage atrial fibrillation patients, particularly regarding its feasibility and safety. On the basis of our heart failure management program [ 25 , 26 ], we conducted the Hospital-Community-Family–Based Telemedicine (HCFT-AF) program incorporating the core elements mentioned above. The aim of this study was to ascertain the feasibility of the HCFT-AF program for implementation of integrated atrial fibrillation care.…”
Section: Introductionmentioning
confidence: 99%
“…There are scarce data on the implementation of such an integrated program to manage atrial fibrillation patients, particularly regarding its feasibility and safety. On the basis of our heart failure management program [ 25 , 26 ], we conducted the Hospital-Community-Family–Based Telemedicine (HCFT-AF) program incorporating the core elements mentioned above. The aim of this study was to ascertain the feasibility of the HCFT-AF program for implementation of integrated atrial fibrillation care.…”
Section: Introductionmentioning
confidence: 99%
“…The telemedical interventional management in heart failure II (TIM-HF 2 ) is a randomized, controlled, parallel-group, unmasked trial, which indicated that a structured remote patient management intervention, when used in a well-defined heart failure population, could reduce the percentage of days lost due to unplanned cardiovascular hospital admissions and mortality of all-causes [ 64 ]. Guo X et al demonstrated the efficacy of a hospital-community-family-based telehealth program for patients with chronic heart failure [ 65 ]. The efficacy of telemedicine in patients with arrhythmia also was proven in several studies.…”
Section: Preliminary Experiences With Using Telemedicine To Manage Stmentioning
confidence: 99%
“…Telehealth visits have been used in multiple diseases to provide nutrition-related interventions. 17 , 18 , 19 Through this type of visit, RDNs can both obtain a thorough history and visualize a patient’s home environment. For example, an RDN providing gluten-free diet education might note that gluten-free flours are directly adjacent to wheat flours.…”
Section: Current Uses Of Telehealthmentioning
confidence: 99%